Teacher wellbeing during the COVID-19 pandemic in Nepal: Comparing the results across the institutions - Khanal, Peshal; Acharya, Sushan; Phyak, Prem (Interdisciplinary Research in Education, 2022)
The COVID-19 pandemic has affected the economic and socio-psychological comforts of teachers in varying degrees. Depending on their job status and the types of institutions, teachers have lost their jobs and faced livelihood challenges. This paper reports the findings of an online survey and focus group discussions exploring various dimensions of teacher wellbeing from both schools and universities in Nepal. The study shows that the wellbeing, particularly economic wellbeing, of teachers from private schools and affiliated colleges is shaken most as their job security is critically affected by the pandemic. Along with the job insecurity and discontinuity of monthly salaries, their stress has elevated due to an added workload for online teaching. In comparison, teachers from community schools and constituent colleges are in a comfortable position; they are regularly paid, and their job is secure despite the school closure in the pandemic. This study raises a critical question about the privatization of schooling to ensure teachers’ wellbeing during a crisis. Based on the findings from this study, we argue that the government and schools should develop the systems to prepare teachers to use ICT tools and other alternative approaches to address learning needs of students during and after crises. More importantly, we suggest that the government should develop policies to create teacher wellbeing funds to support teachers in the crisis.